The Political and Economic Factors of Sanctions against RF - Petrosyan, Gor (YSU Journal of International Affairs, 2022)
The scale of the sanctions that are being imposed on the Russian Federation in 2022 is the largest in the world history. The political and economic consequences of the sanctions are attracting the attention of general public and the scientific community. Studying the impact of sanctions on the Russian Federation is of particular importance both in terms of enriching theoretical and empirical knowledge about sanctions. The article is based on the classical conceptual model of the effectiveness of sanctions put forward by G. Hufbauer, J. Scott, and C. Eliot. In the framework of the article, the author analyzes the structure and share of GDP and foreign trade of the states that apply and are subject to sanctions, as well as short-term, medium-term and long-term political and economic repercussions of sanctions.
Keywords: պատժամիջոցներ; միջազգային հարաբերություններ; քաղաքական ճնշում; տնտեսական մրցակցություն; Ռուսաստանի Դաշնություն